Sample instructional materials for communication arts III (English) in Tiburcio Tancinco Memorial Vocational School, Calbayog City - Nonato, Susana H. (1979)
This study aimed to develop further the language skills needed in the comprehension and use of peculiar linguistic features found in scientific books and articles and also maintain what has been learned by integrating the various skills involved in language learning through the development of a sample of instructional materials in Communication Arts III for use in a vocational high school. Class observations were made in U.P. High School where different natural sciences were used as the core of teaching English. Teacher-made and commercially-made instructional materials in General English were examined. Interviews of English teachers in different curriculum years were also conducted. Reading was given more emphasis in these materials since most scientific articles and books at present are available in English. The sequencing of activities is from easy to complicated tasks, thus giving the students a good grasp of basic ideas and skills needed to comprehend and perform more complex tasks.